Medicinal Chemistry & Chemical Biology Approaches to Investigate Prospective Treatments for CNS Diseases: Dopamine D1 Receptor Positive Allosteric Modulators, Dopamine D2 Receptor Positive & Negative Allosteric Modulators, Dopamine D2 Receptor-Ligand Kinetics - Fyfe, Tim (2019)
The dopamine (DA) D1 and D2 receptors (D1R and D2R, respectively) are G protein-coupled receptors (GPCRs) that are therapeutic targets for the symptomatic treatment of neurological disorders such as schizophrenia (SCZ) and Parkinson’s disease (PD). Classical approaches to GPCR drug discovery have focused on developing orthosteric agents with the capacity to engage the endogenous ligand (dopamine) binding site. Allosteric modulators, molecules that act via a topographically distinct but spatially linked binding site, have been touted as the next generation of CNS therapeutics and may show promise towards the treatment of SCZ and PD. To facilitate an understanding of molecular drug-receptor interactions, such small-molecule allosteric compounds may also be developed and used as biochemical tools, enabling techniques such as rational structure-based drug design or advancement of knowledge regarding key residues responsible for emerging concepts such as functional selectivity. Alternatively, the molecular basis for antipsychotic drug-induced on-target toxicities are also of significant importance in order to facilitate the development of safer therapeutics, and receptor-ligand binding kinetics is a key area of interest. Accordingly, this thesis explores multiple medicinal chemistry and chemical biology approaches to investigate: i) structural drivers of small molecule allosteric pharmacology toward understanding structure-activity-relationships (SAR) for allosteric modulator optimisation and biochemical tool development; ii) the kinetic basis for the “on target” side effect profiles of clinical antipsychotic drugs (APDs) in order to develop novel scaffolds with enhanced efficacy/side-effect profiles.